PERSEPSI APLIKASI STANDART NURSING LANGUAGE DALAM DOKUMENTASI ASUHAN KEPERAWATAN - Rizeki Dwi Fibriansari; Astuti, Anggia; Maisyaroh, Arista; Prasetya Widianto, Eko (Jurnal Penelitian Sains dan Teknologi Indonesia, 2022)
The quality of nursing documentation is strongly influenced by the nurse's compliance with the documentation rules set by the profession and the government. The implementation of nursing care documentation is used as a measuring tool to realize and observe the quality of nursing care services carried out in hospitals. This study aims to identify nurses' perceptions in the application of standard nursing language 3S (SDKI, SLKI, and SIKI) to nursing documentation. This research design was a descriptive study. The subjects of this study were standard nursing language in nursing care documentation. Data analysis in this study was carried out in data reduction, data presentation, and conclusion drawing stages. The data were validated by triangulation and triangulation methods. The results showed that 52% of nurses got their source of information from manuals and only 42.6% of nurses understood the standard application of the 3S nursing language. The cause of this problem is the recording of actions that are not complete and the assessment data is not consistent with the nursing diagnosis. In addition, the recording of nursing actions is too much so it takes up a lot of time for nurses. So, it is necessary to make a standard of nursing language according to 3S which is effective and efficient. Indonesian nursing standard documentation training needs to be carried out to equalize perceptions and have a good impact on nurses' knowledge and service quality.